Effects of particle sizes, resin content and board densities on the properties of phenol formaldehyde particleboard from oil palm trunk particles / Jamaludin Kasim ... [et al.] - Kasim, Jamaludin; Mahmud, Siti Zalifah; Ahmad, Nurrohana; Yamani, Shaikh Abdul Karim; Tamiran, Siti Nor Ain; Shahriman, Nor Suziana; Razak, Nor Ashikin (Research Management Institute (RMI), 2010)
Twenty five year old oil palm trunk supplied by MPOB, Bangi, Selangor, was converted into strands using a disk flaker and into particles using a dust extractor. Particleboard was produced using phenolic resin at 7, 9 and 11% compositions based on particle weight used Particle size variedfrom 1.0-2.0 mm and the board density varied from 500-700 kg m'. No significant improvement in MOR, MOE and IB was observed when the particle size was increased from 1.0 to 2.0 mm. However, with larger particle size the water absorption and thickness swelling properties improved. Increasing the resin content from 7-11 % significantly increases the mechanical properties and improves the water absorption and thickness swelling properties. Increasing the board density results in an increase in MOR, MOE and 1B and a significant increase in the water absorption and thickness swelling properties. Particleboard with a high board density and resin content of more than 9 % met the minimum British Standard requirements.